Clinical and morphological aspects of structures based on fiberglass posts use - Z. S. Khabadze; Ju. A. Generalova; M. G. Sheroziia; A. A. Nedashkovsky; A. N. Gracheva; M. E. Balashova (LLC "Endo Press", 2020)
The aim of this review article is to determine the positive and negative qualities and properties of restoration structures based on fiber posts. After endodontic treatment, it is necessary to strengthen the remaining tissues, since there is an irreversible decrease in the strength characteristics of the tooth.Materials and methods.Produced a systematic review of the literature in the electronic databases Google Scholar and Pubmed. Articles based on the method of using fiberglass posts in clinical practice, analysis of methods for modifying the adhesive preparation of the dentin surface and the post itself, as well as publications related to the discussion of factors that led to the success/failure of the treatment are considered were included.Results. 45 articles were reviewed in the course of information collection. As a result of the submitted articles analysis according to the exclusion criteria, the number of included studies has become 39.Conclusions. Based on the literature studied, the use of structures based on fiber posts is an acceptable method ofpost-endodontic restoration of teeth. But, like any medical manipulation, it has its limitations and side effects.